2015
DOI: 10.1371/journal.pone.0129237
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Id2 Knockdown Whole Tumor Cells and Checkpoint Blockade: A Potent Vaccine Strategy in a Mouse Neuroblastoma Model

Abstract: Tumor vaccines have held much promise, but to date have demonstrated little clinical success. This lack of success is conceivably due to poor tumor antigen presentation combined with immuno-suppressive mechanisms exploited by the tumor itself. Knock down of Inhibitor of differentiation protein 2 (Id2-kd) in mouse neuroblastoma whole tumor cells rendered these cells immunogenic. Id2-kd neuroblastoma (Neuro2a) cells (Id2-kd N2a) failed to grow in most immune competent mice and these mice subsequently developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 56 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…Indirect evidence is observed in the opsoclonus–myoclonus syndrome associated with low or intermediate stage NB. These tumors have profound T-cell infiltrates and are not MYCN amplified ( 21 23 ). The OMS phenomenon is thought to be an autoimmune effect and along with NB that spontaneously regresses this tumor may be an ideal model for studying and understanding tumor immunity as it relates to tumor biology and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence is observed in the opsoclonus–myoclonus syndrome associated with low or intermediate stage NB. These tumors have profound T-cell infiltrates and are not MYCN amplified ( 21 23 ). The OMS phenomenon is thought to be an autoimmune effect and along with NB that spontaneously regresses this tumor may be an ideal model for studying and understanding tumor immunity as it relates to tumor biology and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells can directly escape from T-cell recognition by downregulating MHC class I but upregulating surface ligands, such as PD-L1, CTLA-4, and certain other ligands of inhibitory T-cell receptors, which mediate T-cell exhaustion [ 20 , 29 , 30 ]. Chakrabarti demonstrated that an attenuated Id2-kd whole-cell neuroblastoma vaccine was safe in mice and could induce a broad tumor-specific cellular immunity, which protected against tumor formation in prophylactic tumor models and eradicated large established neuroblastoma tumors in combination with an anti-CTLA-4 antibody [ 31 ]. A recent study showed that the IL-27/STAT3 axis induced the expression of PD-L1/2, and that STAT3 blockage reversed T cell exhaustion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A) Expression of ICD markers as a function of thermal dose described in terms of cumulative equivalent minutes at 43 °C; a thermal dose parameter (CEM43). [38] The grey shaded area represents the region of increased ICD elicited by PBNP-PTT. B) % Survival of mice (at 100 d) challenged with Neuro2a tumors that were vaccinated with PBNP-PTT-treated Neuro2a cells.…”
Section: Methodsmentioning
confidence: 99%
“…PBNP‐PTT‐treated Neuro2a cells exhibit a thermal “window” of ICD, which is associated with improved protection against tumor challenge. A) Expression of ICD markers as a function of thermal dose described in terms of cumulative equivalent minutes at 43 °C; a thermal dose parameter (CEM43) . The grey shaded area represents the region of increased ICD elicited by PBNP‐PTT.…”
mentioning
confidence: 99%